Nursing Procedures in Special Areas (2nd Edition) - Saloma, Pawi; Rekaya Vincent, Balang; Sidiah, John Siop; Jane, Buncuan; Dev Nath, Kaushal (UNIMAS Publisher, 2016)
This handbook is a manual on clinical procedures commonly carried out in the hospital settings. It serves as a reference for nursing students during their clinical placement in specialised areas.